Atticus on the Status of Platonic Ideas - Chiara Bonuglia (Lexicon Philosophicum)
Atticus’ fragments clearly testify that his commitment to a literal interpretation of the Timaeus along the lines of the craftsman model. Atticus assumed the three-principled theory according to which God, ideas-paradigms, and matter are the ‘causes’ of the sensible world. Nevertheless, the role of the παράδειγμα within metaphysical reality is difficult to define, especially because when Atticus refers to ideas, he seems to support, on one hand, the idea that Forms coincide to god’s thoughts but, on the other hand, he seems to refuse this identification. This issue is complicated by the fact that Atticus refers to ideas as παραίτια (collateral causes: fr. 9). This expression doesn’t allude to a downgrading of ideas – as some scholars have argued – but it regards only the cosmological causation.